1997
DOI: 10.1897/1551-5028(1997)016<1749:elsmoj>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Early Life-Stage Mortalities of Japanese Medaka (Oryzias Latipes) Exposed to Polychlorinated Diphenyl Ethers

Abstract: Polychlorinated diphenyl ethers (PCDEs) are a group of compounds that resemble polychlorinated dibenzofurans in structure that have been detected at ppb concentrations in fish from the Great Lakes. The objective of this project was to determine the toxicological significance of PCDE residues in fish. PCDE congener 77 (3,3Ј,4,4Ј-tetrachlorodiphenyl ether), congener 71 (2,3Ј,4Ј,6-tetrachlorodiphenyl ether), congener 118 (2,3Ј,4,4Ј,5-pentachlorodiphenyl ether), and congener 105 (2,3,3Ј,4,4Ј-pentachlorodiphenyl) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The LC50 values for the PCAs are at least three to six orders of magnitude higher than those observed for chlorinated dioxin and furan congeners, polychlorinated biphenyl congeners, or polychlorinated diphenyl ether congeners using Japanese medaka eggs ( Table 6). The LC50 determined for TCDD in this study is in the range reported in other studies for TCDD using Japanese medaka eggs [24][25][26][27][28]. As well, Wisk and Cooper [24] reported an ED 50 of 0.24 ng/g for TCDD equivalents in larvae, which is similar to the concentration in eggs at the LOEC in tissue in this study ( Table 5).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The LC50 values for the PCAs are at least three to six orders of magnitude higher than those observed for chlorinated dioxin and furan congeners, polychlorinated biphenyl congeners, or polychlorinated diphenyl ether congeners using Japanese medaka eggs ( Table 6). The LC50 determined for TCDD in this study is in the range reported in other studies for TCDD using Japanese medaka eggs [24][25][26][27][28]. As well, Wisk and Cooper [24] reported an ED 50 of 0.24 ng/g for TCDD equivalents in larvae, which is similar to the concentration in eggs at the LOEC in tissue in this study ( Table 5).…”
Section: Discussionsupporting
confidence: 86%
“…Hatching success (by day 20) was low for many of the treatments and was well below the hatching success reported in other studies on Japanese medaka eggs [24][25][26][27][28]. The average time of hatching (Ͼ15 d) was also longer than what is normally [32] and assuming the chemical is a narcotic.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations